ANALISIS PENGARUH HARGA, KUALITAS, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN YANG DIMEDIASI OLEH MINAT BELI LAMPU PANDAWA LED - Govanda Elcovano Adenza Faradz; Nur Achmad (POLITEKNIK LP3I JAKARTA, 2024)
This quantitative study aims to analyze the effect of price, quality, and promotion on purchasing decisions mediated by buying interest in Pandawa Led lamps. The population in this study were consumers of Pandawa LED lamps at the Gema Lawu Elektronik Plaosan store, from which data was taken in part with a Likert-scale questionnaire. The sampling technique in this study was non probability sampling with a purposive sampling approach. The data analysis technique used in this study is to use PLS-SEM analysis consisting of two Outer model and Inner model. The results showed that price, product quality and promotion had a positive and significant effect on purchasing decisions. Likewise, price, product quality and promotion have a positive and significant effect on purchase intention. The same results on the mediating variable can be explained that buying interest mediates the influence between price, product quality and promotion variables on purchasing decisions.